Simbología de poder en Guayabo de Turrialba - Hurtado de Mendoza, Luis (2013)
Inferences are made on the symbolic purpose of the architectonic compounds at the Guayabo de Turrialba National Monument, in regard to rank and sociopolitical power in the prehispanic chiefdom society of the Reventazón watershed (200 B.C.-A.D. 1300). Data analyses are performed on the cultural history, chronology of monumental architecture, size and volume of public works, and estimated requirements of labor and building materials.